Community preferences for a social health insurance benefit package: an exploratory study among the uninsured in Vietnam - Nguyen, Hoa Thi; De Allegri, Manuela (BMJ global health, 2017)
Understanding public preferences in terms of health benefit packages (HBPs) remains limited, yet gathering community insights is an important endeavour when developing people-centred health systems and moving towards universal health coverage. Our study aimed to address this gap in knowledge by eliciting community preferences for the social health insurance benefit package among the uninsured in Vietnam. We adopted a mixed methods approach that included a ranking exercise followed by focus group discussions. We collected quantitative and qualitative data from 174 uninsured people in Bac Giang, a province in northern Vietnam. Study participants were purposively selected from 12 communities and assembled in 14 group sessions that entailed three stages: participants first selected and ranked benefit items individually, then in groups and finally they engaged in a discussion regarding their decisions. The majority of respondents (both as individuals and as groups) preferred an HBP that covers both curative and preventive care, with a strong preference for the inclusion of high-cost care, resulting from rare and costly events (inpatient care), as well as frequent and less costly events (drugs, tests and outpatient care). The process of group discussion highlighted how individual choices could be modified in the context of group negotiation. The shift in preferences was motivated by the wish to protect low-income people from catastrophic expenditure while maximising community access to vital yet costly healthcare services. Future research, interventions and policies can built on this initial exploration of preferences to explore how stakeholders can engage communities and support greater public involvement in the development of HBPs in Vietnam and other low-income and middle-income countries.